Overall survival advantage of chemotherapy and radiotherapy in the perioperative management of large extremity and trunk soft tissue sarcoma; a large database analysis. Issue 2 (August 2017) - Mahmoud, Omar; Tunceroglu, Ahmet; Chokshi, Ravi; Benevenia, Joseph; Beebe, Kathleen; Patterson, Francis; DeLaney, Thomas F.
Abstract: Purpose: Intergroup 9514 reported promising outcomes with neoadjuvant chemoradiotherapy for large extremity/trunk soft tissue sarcoma (ESTS). One decade later, optimum integration of chemotherapy and radiotherapy into the perioperative management of ESTS remains to be defined. Methods: The National Cancer Data Base was used to identify 3422 patients who underwent resection for large (>8 cm) high-grade STS between 2004 and 2013. Chi-square analysis was used to evaluate distribution of patient and tumor related factors within treatment groups while multivariate analyses were used to determine the impact of these factors on patient outcome. The Kaplan Meier method and Cox proportional hazards model were utilized to evaluate overall survival according to treatment regimen, with a secondary analysis based on propensity score matching to control for prescription bias and potential confounders imbalance. Results: Hazard ratio for death was reduced by 35% with radiotherapy and 24% with chemotherapy, compared to surgery alone. Combination therapy incorporating both modalities improved 5-yr survival (62.1%) compared to either treatment alone (51.4%). The sequencing of chemotherapy and radiotherapy or whether they were delivered as adjuvant vs. as neoadjuvant therapy did not affect their efficacy. Age > 50 years, tumor size > 11 cm, and tumor location on the trunk/pelvis were poor prognostic factors. Conclusion: Our analysis suggests that adjunctive modalities are both critical in the treatment of large high-grade ESTS, improving survival when used individually and demonstrating synergy in combination, regardless of sequencing relative to each other or relative to surgery; thus providing a framework for future randomized trials.